Penggunaan Seni Mural Dalam Memperkenalkan Sejarah Kepada Siswa Sekolah Dasar Negeri X Kabupaten Tangerang Banten - Lengsi Manurung; Hugo Aries Suprapto; Sigit Widiyarto (Jurnal Ilmiah Wahana Pendidikan, 2023)
Learning requires creativity, innovation, and brilliant ideas so that students are interested in learning more. Media that is boring will make students lazy to learn and quickly get bored. The purpose of this research is to find out the mural learning process at SDN X Tangerang Regency and to find out the effectiveness of mural media on history learning. The methodology in this research is a qualitative method. Data collection by interview, documentation and literature study. The informants were 5 teachers and 5 class V SDN X Tangerang Regency students. The study results show that the mural learning process includes drawing, understanding images and making reports based on the results of observing images. There is an increase in value before and after using mural media.